Variability of the total oil content and fatty acid profile of creole avocados from Nuevo Leon, Mexico = Variabilidad del contenido total de aceite y perfil de ácidos grasos de aguacates criollos de Nuevo León, México - Acosta Díaz, Efraín
Introduction. The State of Nuevo Leon is considered the depositary of a wide genetic diversity of creole avocados (Persea americana var drimyfolia). Objective. The aim of this work was to determine the variability of the total oil content and the fatty acids profile in creole avocados from Nuevo Leon, Mexico. Materials and methods. During the spring and summer of 2016, 36 varieties of creole avocados were collected in the northern and southern region of the State of Nuevo Leon, Mexico for chemical characterization. The commercial variety "Hass" was included as a control. To determine the variability that exists in the content of total oils and fatty acids in the collected materials, analyzes of the main components and conglomerates were carried out. Results. Six fatty acids were detected in the total oil of the creole avocados: palmitic, stearic, oleic, palmitoleic, linoleic and linolenic. The outstanding varieties were "Platano temprano", "Platano delgado", "Huevo de toro", "Cuerno", "Pato", and "Especial", which presented an average of 17.28, 24.93 and 66.29 % more in the content of oleic, linoleic and linolenic acids respectively, and an average of 28.12 % less stearic acid compared to the commercial variety "Hass". According to the analysis of main components, materials with high oleic acid content usually have low palmitic and palmitoleic acid contents. The dendrogram presented six groups within the evaluated materials, most of the outstanding materials are located in groups one and four. Conclusion. High variability in the content of total oils and fatty acids was determined in creole avocados from Nuevo Leon. Therefore, they are considered promising for their incorporation into genetic improvement programs.